2013
DOI: 10.1111/jocn.12431
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of pregnant teenagers' views of the future and their decisions to continue or terminate their pregnancy: implications for nursing care

Abstract: The findings suggest that working with teenage girls to clarify their views of the future may be useful both in preventing future unwanted pregnancy and in supporting teenagers in making pregnancy decisions. Supporting pregnant teenagers in distancing themselves from negative stereotypes of teenage mothers may also be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…Less attention has been paid to what happens during the time in between the discovery that one is pregnant and the decision to carry that pregnancy to term and become a parent. The literature that examines teenagers' unintended pregnancy resolution process rarely uses individual, in-depth interview data and most is not US-focused (Bell, Glover, and Alexander 2014;Gomez-Scott and Cooney 2014;Greene 2006;Hoggart 2012;Lee et al 2006;Mantovani and Thomas 2014;Tatum et al 2012). Of the studies that focus on teenage pregnancy resolution in the USA in the past 20 years, most take a comparative, quantitative approach, examining selected demographic and personal characteristics of pregnant teenagers who choose a variety of alternatives, such as abortion, adoption or parenthood (Adamczyk and Felson 2008;Coleman 2006;Gomez-Scott and Cooney 2014;Madkour, Xie, and Harville 2013;Moore and Davidson 2002;Murry 1995).…”
Section: Adolescent Pregnancy Resolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…Less attention has been paid to what happens during the time in between the discovery that one is pregnant and the decision to carry that pregnancy to term and become a parent. The literature that examines teenagers' unintended pregnancy resolution process rarely uses individual, in-depth interview data and most is not US-focused (Bell, Glover, and Alexander 2014;Gomez-Scott and Cooney 2014;Greene 2006;Hoggart 2012;Lee et al 2006;Mantovani and Thomas 2014;Tatum et al 2012). Of the studies that focus on teenage pregnancy resolution in the USA in the past 20 years, most take a comparative, quantitative approach, examining selected demographic and personal characteristics of pregnant teenagers who choose a variety of alternatives, such as abortion, adoption or parenthood (Adamczyk and Felson 2008;Coleman 2006;Gomez-Scott and Cooney 2014;Madkour, Xie, and Harville 2013;Moore and Davidson 2002;Murry 1995).…”
Section: Adolescent Pregnancy Resolutionmentioning
confidence: 97%
“…Some of this research explores pregnant teenagers' views of the future and related perceptions regarding the opportunity costs of having a child in adolescence, finding that those with parents with higher levels of education and cogent, long-term plans that include academic aspirations for themselves are more likely to terminate an unintended pregnancy (Bell, Glover, and Alexander 2014;Gomez-Scott and Cooney 2014). Scholars who examine the influence of religious beliefs observe that pregnant young women who identify with a conservative Protestant denomination are far less likely to terminate a pregnancy than other pregnant teenagers (Adamczyk and Felson 2008).…”
Section: Adolescent Pregnancy Resolutionmentioning
confidence: 98%
“…Although in this study we have interviewed only the adolescents who have chosen to keep the pregnancy, we note that only four of them reported having thought about the possibility of an abortion. Bell et al 2 have observed that, in a country where abortion is legal, young persons with more plans for the future, especially focusing on work and career, tend to choose abortion more.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent pregnancy is often presented as a significant problem with negative consequences for young mothers and their children (Duncan 2005;Yardley 2008;Harden et al 2009;Macvarish 2010;Bell et al 2014;Ellis-Sloan 2014). Poverty, maternal mental health, unemployment, and child health deficits have been associated with teenage pregnancy over the last two decades (Social Exclusion Unit: SEU 1999;Department for Education and Skills 2006;Mental Health Foundation 2013;Public Health England 2016).…”
Section: Introductionmentioning
confidence: 99%